Determination of The Optimum Conditions for Urease Extraction from Chickpea Seeds Using (Design Expert Software) - S. Kurdi, Sarah; J. M-Ridha, Mohanad (Al-Khwarizmi Engineering Journal, 2024)
This study aimed to utilise response surface methodology (RSM) to determine the optimal conditions for extracting urease from a plant source and evaluate its biochemical properties. Chickpea seeds were selected as the source of urease. Results showed that chickpea seeds had a high enzyme activity (3.99 U/mg protein) under the best extraction conditions of pH 7.99, tris base buffer concentration of 0.2, time of 60 minutes and ratio of 1:13 (g: mL). When a second-order polynomial model was used, the predicted correlation coefficient (pred. R2) was 0.8477, the adjusted correlation coefficient (adj. R2) was 0.9333 and the correlation values (R2) were 0.9665, indicating that the predicted models and experimental values agreed very well. The method has the potential to enhance the cost-effectiveness of enzyme production through large-scale manufacturing and offers an economical alternative to other techniques.